Viabilitas Spermatozoa Babi dalam Pengencer BTS (Beltsville Thawing Solution) yang Dimodifikasi pada Penyimpanan Berbeda - N.L G Sumardani; L Y Tuty; P H Siagian (Media Peternakan, 2008)
The optimal storage temperature for preserve boar semen is 17-18°C. The temperature fluctuations can decrease sperm viability. The aim of this study was to obtain a boar semen extender for Artificial Insemination (AI) at a certain distance area. The observation was based on the sperm viability in modified Beltsville Thawing Solution (BTS) extender in different storage, and the effect of storage system i.e.: room temperature (22°C) and styrofoam box (18°C) were conducted for this purpose. The research used a completely randomized design (CRD) with two factorial i.e.: BTS and M-BTS extender (F1), room temperature and styrofoam box (F2). Semen from three years old Yorkshire boars (n = 3) were collected twice a week by glove hand method. Semen characteristics and their quality were evaluated macro and microscopically. These semen were added with BTS and M-BTS extender up to fourfold volume (ratio 1 : 3). This is based on the assumption of AI dose of 2 - 3 x 109cells/80ml and the sperm motility and viability were evaluated every six hours for 24 hours observation. The results showed that fresh semen characteristics were good, with the percentage of sperm motility 65.56±2.55% and sperm viability of 87.70±2.87%. The best extender found in this experiment of 24 hours observation was BTS extender with sperm motility 53.33±3.33% in styrofoam box. In conclusion, BTS extender can maintain the quality of spermatozoa stored in styrofoam box for about 24 hours with sperm motility 40%-50%, and the styrofoam box can be used as an alternative container for insemination program in the field. Key words: sperm viability, semen extender, storage, boar sperm